2022
DOI: 10.1128/iai.00530-21
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Streptococcus pneumoniae to Hypothiocyanous Acid Generated by Host Peroxidases

Abstract: Streptococcus pneumoniae is a serious human respiratory pathogen. It generates hydrogen peroxide (H 2 O 2 ) as part of its normal metabolism, yet it lacks enzymes that remove this oxidant. Here we show that lactoperoxidase and myeloperoxidase, two host enzymes present in the respiratory tract, convert bacterial H 2 O 2 into HOSCN that S. pneumoniae can resist. We found that incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 70 publications
2
28
0
Order By: Relevance
“…Initial insight came from a study on H 2 O 2 -producing oral streptococci, where some species were shown to have an uncharacterized HOSCN oxidoreductase activity that correlated with their ability to survive HOSCN (26). We noted that S. pneumoniae survives HOSCN exposure much better than the opportunistic and HOSCN reductase-negative respiratory pathogen P. aeruginosa (20), which unlike S. pneumoniae, does not colonize and rarely causes disease in healthy people. We have now identified and characterized a HOSCN reductase in S. pneumoniae that contributes to the ability of this deadly pathogen to tolerate HOSCN.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Initial insight came from a study on H 2 O 2 -producing oral streptococci, where some species were shown to have an uncharacterized HOSCN oxidoreductase activity that correlated with their ability to survive HOSCN (26). We noted that S. pneumoniae survives HOSCN exposure much better than the opportunistic and HOSCN reductase-negative respiratory pathogen P. aeruginosa (20), which unlike S. pneumoniae, does not colonize and rarely causes disease in healthy people. We have now identified and characterized a HOSCN reductase in S. pneumoniae that contributes to the ability of this deadly pathogen to tolerate HOSCN.…”
Section: Discussionmentioning
confidence: 97%
“…We recently reported that S. pneumoniae is relatively tolerant of HOSCN, when compared with another respiratory microbe Pseudomonas aeruginosa ( 20 ). This raises the question as to what mechanisms are responsible for HOSCN tolerance.…”
mentioning
confidence: 99%
“…Therefore, the ability of P. aeruginosa , a major pathogen of the CF lung (Greenwald & Wolfgang, 2022), to respond to and survive stress caused by HOSCN is important to understand. P. aeruginosa is substantially more sensitive to HOSCN than S. pneumoniae (Shearer, Kaldor, et al, 2022), and is more sensitive at pH 6.8 than at pH 7.4 (Chandler et al, 2013), consistent with protonation of HOSCN being an important determinant of its toxicity for bacteria.…”
Section: Introduction To Hypothiocyanitementioning
confidence: 95%
“…HOSCN is much less reactive than HOCl (Pattison et al, 2012), which may reduce the impact of cell density in HOSCN stress assays. Experiments with S. pneumoniae suggest that bacteria react only slowly with HOSCN (Shearer, Kaldor, et al, 2022; Shearer, Pace, et al, 2022), suggesting that even bolus addition of HOSCN may result in a relatively slow flux of oxidant into the cells.…”
Section: Introduction To Hypothiocyanitementioning
confidence: 99%
See 1 more Smart Citation